1994
DOI: 10.1002/1097-0142(19940901)74:5<1556::aid-cncr2820740511>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Time trend and the age-period-cohort effect on the incidence of histologic types of lung cancer in connecticut, 1960-1989

Abstract: Background. Recent epidemiologic studies have suggested changing patterns of lung cancer incidence by histologic type. The observed time trends have been attributed to a change in the rate of cigarette smoking, changes in exposure to new environmental carcinogens, and changes in the criteria for the histopathologic diagnosis of lung cancer. The current study was designed to examine the incidence patterns of lung cancer by histologic type in Connecticut and to use this information to project the future trend of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
1
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 48 publications
6
43
1
8
Order By: Relevance
“…In the US and Europe, several hospital-based studies, [3][4][5][6] autopsy series 7) and population-based studies [8][9][10][11][12][13][14][15][16] have examined the trends of lung cancer incidence by histologic type. In Asian countries there have been hospitalbased studies, [17][18][19][20] and a population-based study.…”
supporting
confidence: 88%
“…In the US and Europe, several hospital-based studies, [3][4][5][6] autopsy series 7) and population-based studies [8][9][10][11][12][13][14][15][16] have examined the trends of lung cancer incidence by histologic type. In Asian countries there have been hospitalbased studies, [17][18][19][20] and a population-based study.…”
supporting
confidence: 88%
“…Mudanças significativas na incidência dos maiores tipos histológicos do câncer do pulmão, principalmente do adenocarcinoma, têm sido observadas em alguns paí-ses (57,58) .…”
Section: Ix) Fatores Genéticosunclassified
“…6 The changing histological patterns in lung cancer probably relate to changes in the composition of cigarettes. 7,8 As only 10% of cigarette smokers develop lung cancer, 9 it is suggested that genetic factors may be a contributing factor. Segregation analysis of lung cancer also supports the existence of heritable effects.…”
mentioning
confidence: 99%